The Impact of Courtyard Spatial Characteristics Across Historical Periods on Summer Microclimates: A Case Study from China - Qian Zhang; Xuan Ma; Duo Xu; Dian Zhou; Yujun Yang; Weile Jiang (Buildings)
This study investigates the impact of spatial changes over a 400-year period on the summer microclimate of a residential courtyard in China. Using ENVI-met simulations, we analyze how factors such as courtyard orientation, building height, and opening positions affect the thermal environment. The results show that east–west-oriented courtyards experienced 0.2–0.4 °C lower daytime temperatures compared to north–south ones. Additionally, taller surrounding buildings increased the courtyard’s average daytime temperature by approximately 0.3–0.5 °C, while courtyards with a single opening facing the prevailing wind maintained the lowest temperatures. These findings underscore the importance of historical spatial characteristics in shaping microclimates and offer key insights for contemporary urban planning. By incorporating design strategies based on these historical spatial features, such as optimizing courtyard orientation, enhancing building height variability, and creating appropriate openings for natural ventilation, urban planners can improve microclimate conditions, reduce reliance on mechanical cooling, and enhance energy efficiency. This approach not only contributes to lowering carbon emissions but also boosts resilience to extreme heat events in urban areas, especially in regions facing rapid urbanization and climate change challenges.